Elements of Sales Growth, Net Profit Margin, Return on Equity, Firm Value, and Dividend Yield on Stock Returns - Bambang Abdullah R; Ferri Kuswantoro; Titop Dwiwinarno; Burhanudin; Eni Andari (Ridwan Institute, 2026)
This study aimed to determine the factors influencing stock returns in financial sector companies listed on the Indonesia Stock Exchange. A total of 17 (seven teen) financial institutions were sampled using a purposive sampling method for secondary data obtained from Indonesia Stock Exchange. The data processings were supported by eviews 12 software and microsoft office. Prior to analysis, the research model was tested using the chow and hausman tests and classical assumptions. The results showed that partially, sales growth, net profit margin, return on equity, and dividend yield had a significant positive effect on stock returns with a probability of < 0.05, while firm value did not effect. Collectively the F-test showed that all variables had a positive significant effect on stock returns. The study was conducted in the banking sector from 2021 to 2022 period.